Impactof Organizational Justice on Organizational Citizenship Behavior: A case study on hotels in Iraq (International Journal of Psychosocial Rehabilitation, 2020)
The study deals with one of the most important concepts in human resource management in general and influencing it in a high rate in the case of Iraqi hotels in particular, Where the study touched upon the concepts of organizational justice as an independent variable and the behavior of citizenship as a dependent variable in terms of the nature of the influence relationship between them And with a real management problem inside Iraqi hotels, through which a number of hypothesis were made to measure them And knowing whether there are moral effects on the level of the main and sub variables This study was applied to a group of Iraqi hotels as the study community By designing the questionnaire using a Likert scale and distributing (150) forms to workers in those hotels And then collect data and analyze it statistically using the program (spss v.25)